1999
DOI: 10.1007/bf02443430
|View full text |Cite
|
Sign up to set email alerts
|

Does acetylcholinesterase secretion involve an ADAMs-like metallosecretase?

Abstract: SummaryThe ADAMs (A Disintegrin And Metalloprotease-like) family is a large and rapidly expanding group of metalloproteinases with structural similarity. They are normally characterized by the presence of a proteolytic domain and disintegrin and signalling domains. Although 21 ADAMs proteins have been already cloned to date, in most cases their natural substrates are unknown. The best characterized representative of the mammalian ADAMs family is the TNF-~ converting enzyme (TACE). TACE is an integral membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Analysis of the effects of acute hypoxia on the mature brain of adult animals performed in the KOCHKINA et al second part of this study also revealed that oxygen deficit in the brain tissue leads to a decrease in the activity of the membrane bound AChE in the sensorimotor cortex already 30 min after the exposure remaining decreased at least for 24 h. The activity of soluble and membrane bound BChE 30 min after hypoxic insult was found to be decreased remaining at that level 24 h later, while soluble AChE activity was higher 30 min after hypoxia compared to controls and decreased only after 24 h. Such simultaneous increase in the activity of soluble AChE and reduced activity of the membrane bound form can be explained by an increased processing of AChE molecules anchored in the cellular membranes by the α-secretase mechanism and shedding of its ectodomain into the extracellular medium [10]. As we have shown earlier, hypoxia leads to an increased expression of one of the enzymes of a metalloproteinase family, namely ADAM17, which is capable of cleaving a variety of the membrane bound proteins [38].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Analysis of the effects of acute hypoxia on the mature brain of adult animals performed in the KOCHKINA et al second part of this study also revealed that oxygen deficit in the brain tissue leads to a decrease in the activity of the membrane bound AChE in the sensorimotor cortex already 30 min after the exposure remaining decreased at least for 24 h. The activity of soluble and membrane bound BChE 30 min after hypoxic insult was found to be decreased remaining at that level 24 h later, while soluble AChE activity was higher 30 min after hypoxia compared to controls and decreased only after 24 h. Such simultaneous increase in the activity of soluble AChE and reduced activity of the membrane bound form can be explained by an increased processing of AChE molecules anchored in the cellular membranes by the α-secretase mechanism and shedding of its ectodomain into the extracellular medium [10]. As we have shown earlier, hypoxia leads to an increased expression of one of the enzymes of a metalloproteinase family, namely ADAM17, which is capable of cleaving a variety of the membrane bound proteins [38].…”
Section: Discussionmentioning
confidence: 87%
“…Alternative splicing of the AChE gene product leads to formation of different AChE forms, the major one being the tetrameric T-form anchored in the cell membrane via two proteins PRiMA and ColQ [9]. Although there are data demonstrating that neuronal cells upon various stimuli can release soluble form of AChE, the exact mechanism of its formation and secretion is still unknown although there is evidence that some proteolytic enzymes, for example the α-secretase of amyloid precursor protein, might be involved in this process [10,11]. In the brain AChE and ВChE have different localisations.…”
Section: Introductionmentioning
confidence: 99%
“…These effects were not affected by the classical AChE active site inhibitors edrophonium and tacrine but were abolished in the presence of the peripheral anionic binding site ligands propidium and gallamine [97]. It is still not clear what is the molecular mechanism of the noncholinergic effects of AChE but it seems that post-translational proteolytic release of a soluble form of the enzyme from the cell surface is required for its neuritogenic activity [65]. The ability of AChE to affect cell proliferation, differentiation and responses to various factors also depends on the products of the alternative splicing of the AChE gene and, in particular to the homology of these products with gliotactin, glutactin and the neurexins [90].…”
Section: Adhesive Properties and Protein-protein Interactionsmentioning
confidence: 96%
“…Although the detergent-soluble form of AChE contains a structural subunit that serves as membrane anchor, no anchor was detected in soluble AChE. Analysing the possible mechanism of secretion of the soluble form of AChE from the surface of neuronal cells, we have suggested that a metallosecretase might be involved in this process [65] probably similar or identical to the a-secretase involved in APP metabolism.…”
Section: Localisation and Physiological Rolesmentioning
confidence: 99%
“…Our data also testify that hypoxia significantly modifies the activity of α-secretase, which is important in production of the main pool of soluble APP and prevention of the formation of Аβ. The deficit of this enzyme might also lead to a decreased production of soluble AChE [73]. In general, the increase of APP content in the brain and reduction in its nonamyloidogenic processing by α-secretase after prenatal hypoxia could predispose to a shift in amyloid metabolism in the brain toward the processes initiating development of AD (Figure 2).…”
Section: Changes At the Molecular And Biochemical Levelsmentioning
confidence: 99%